1982
DOI: 10.2508/chikusan.53.699
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Estrogen on Triglyceride Metabolism in Chick Liver

Abstract: The present experiments were carried out on the relationship between triglyceride synthesis and fatty acid oxidation in liver of chicks treated by estrogen, in order to study on the mechanism underlying estrogen-induced hypertriglyceridemia. Estrogen treatment increased the incorporation of 14C-acetate into fatty acid and of 14C-palmitate into triglyceride in vivo and in vitro. This result suggests that triglyceride synthesis is stimulated by estrogen.The 14C incorporation from [1-14C] palmitate into CO2 in vi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

1986
1986
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 7 publications
0
4
0
Order By: Relevance
“…Estrogen is generally considered as a major factor regulating the expression of genes related to lipid metabolism in chicken livers 39,40 . To explore the regulatory mechanisms of three gene families involved in the TG synthesis pathway, 10-week-old pullets were treated with different doses of 17β-estradiol for 12 h. After the treatment, serum biochemical parameters of the chickens were determined.…”
Section: Resultsmentioning
confidence: 99%
“…Estrogen is generally considered as a major factor regulating the expression of genes related to lipid metabolism in chicken livers 39,40 . To explore the regulatory mechanisms of three gene families involved in the TG synthesis pathway, 10-week-old pullets were treated with different doses of 17β-estradiol for 12 h. After the treatment, serum biochemical parameters of the chickens were determined.…”
Section: Resultsmentioning
confidence: 99%
“…For comparison, in chickens a strong stimulation of fat synthesis, e.g. by oestrogens, was related with an about 45% rise in liver weight, about threefold increase of fat tissue weight, about fortyfold increase of serum TG level (Hasegawa et al, 1982).…”
Section: Discussionmentioning
confidence: 96%
“…Estrogen is vitally important for sexual maturity and the development of the female reproductive system [ 11 , 12 ]. It is generally believed that the estrogen level of hens rises significantly during the egg-laying period, as do many of the genes and their products involved in hepatic lipid and fatty acid metabolism in liver tissue [ 13 , 14 , 15 ]. Our previous liver transcriptome research in laying hens showed that ELOVL5 increased by 1.98-fold in peak-laying-period hens (30 weeks old) compared with pre-laying-period hens (20 weeks old) [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…Our previous liver transcriptome research in laying hens showed that ELOVL5 increased by 1.98-fold in peak-laying-period hens (30 weeks old) compared with pre-laying-period hens (20 weeks old) [ 16 ]. An increasing number of studies have demonstrated that miRNA serve as important regulators in lipid and fatty acid metabolism [ 11 , 12 , 13 , 14 ]. Our recent study revealed several differently expressed miRNA in liver between pre- and peak-laying-period hens, which suggested that hepatic miRNA might play a role in the regulation of hepatic lipid and fatty acid synthesis [ 17 ].…”
Section: Introductionmentioning
confidence: 99%